Flexible office meeting table (FLOMITA) / Mohd Shafie Ansar and Mustafa Tahang - Ansar, Mohd Shafie; Tahang, Mustafa (2009)
This study discuss about office table where that bring something different in furniture making industry, especially in Malaysia. This project also present about design that will be bring out the revolution in this sector. The furniture is a flexible table and it is built with prototype measurement and using combination between Medium Density Fiberboard (MDF), plywood and solid wood such as Shorea spp. other than that this new furniture has a two function in one of office table. That means, from the personal table we can used with meeting table for discussing. The efficient of this new furniture design will be bring the revolution in world furniture industry. The flexible meeting office table can reduce expenses cost to buying more furniture in office, but it have a high if esthetical value and indirectly the new design in office furniture is look a very special.